FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN LANSIA KE POSYANDU LANSIA DI KELURAHAN PELINTUNG - Nurul " Athfal; Erwin " "; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Posyandu is an integrated service post for elderly people where they can get health care. Average visit the elderly in posyandu still lacking, this is caused by a variety of physical conditions, distance from the house away to Posyandu. This research is a quantitative research using descriptive retrospective approach. This study aimed to describe factors that affect the elderly to visit the Posyandu elderly at Kelurahan Pelintung. The number of participants in this study were 62 people who were taken by random sampling technique. The analysis used univariate analysis to determine the frequency distribution and bivariate analysis using chi-square test for to determine the relationship between motivation, health services, family support, distance / aksebilitasi with a visit to the Posyandu elderly. Univariate study results illustrate that the majority of respondents were female which amounted to 41 respondents (66.1%), are in the age range 56-65 years (elderly end) in 38 respondents (61.3%), the majority of respondents are married as many as 25 respondents (40.3%) and the majority of respondents still working as much as 32 respondents (51.6%). The results of the bivariate analysis research shows that there is a relationship between motivation (p value 0.017) with a visit elderly and there is no relationship between the health service (p value 1.00), family support (p value 0.407), distance / aksebilitasi (p value 0.354). Suggested for health workers, especially nurses to improve health care for the elderly through Posyandu. Keywords: Elderly, motivation, posyandu.